Substituting time-consuming pencil drawings in arthropod taxonomy using stacks of digital photographs - Coleman, Charles O. (Zootaxa, 2006)
The most time-consuming part of a taxonomic description is making the illustrations. This contribution shows how to save time by omitting the pencil drawings of arthropod appendages and replacing them by stacks of microphotographs. These are imported into a drawing software package on a computer in order to make a publication-ready line drawing, a technique described in detail in Coleman (2003). The photographic method requires a special treatment of the appendages which is also shown.